Autism and Employment: Implications for Employers and Adults with ASD. - Solomon, Calvin (Journal of Autism & Developmental Disorders, 2020)
A small but growing body of research has been conducted on vocational outcomes for adults with Autism Spectrum Disorder (ASD); however, limited resources have been directed towards understanding outcomes for competitive employers. While ASD does present with a range of social communication and adaptive behavior deficits, adults on the spectrum may be extremely efficient, trustworthy, reliable, and cost-effective employees. Nevertheless, fewer than half of young adults with ASD maintain a job. Many businesses are unwilling to hire these capable candidates, concerned among other things about an increase in supervision costs and a decrease in productivity. This is a bias based on misperceptions; the financial and social benefits of hiring adults with ASD, for businesses and the individual, often outweigh the costs.